Telemetric Assessment of Referred Vaginal Hyperalgesia and the Effect of Indomethacin in a Rat Model of Endometriosis - Dmitrieva, Natalia; Faircloth, Elizabeth K.; Pyatok, Stephen; Sacher, Frank; Patchev, Vladimir K. (Frontiers in Pharmacology, 2012)
Symptoms of endometriosis, among others, include pelvic/abdominal and muscle pain. Non-steroidal anti-inflammatory agents are first-line treatment for this pain. Similar to women, rats with surgically-induced endometriosis (ENDO), but not its surgical control, exhibit vaginal hyperalgesia, which in rats is evidenced by a decreased threshold for the visceromotor response (VMR) induced by vaginal distention. Here we assess the VMR in rats with implanted probes that telemetrically transmit EMG activity from the abdominal muscle. The feasibility and sensitivity of this technique for monitoring the VMR threshold across the estrous cycle and the influence of Indomethacin on ENDO-induced vaginal hyperalgesia were evaluated. VMR thresholds in response to vaginal distention with an infusion pump were measured in different estrous stages. Indomethacin (5 or 10 mg/kg i.p.or s.c.) was injected in proestrous rats and 40-60 min later the VMR threshold was measured. The VMR threshold varied across the estrous cycle only in ENDO rats, being lowest in proestrus. Indomethacin increased this threshold in proestrous ENDO rats. These results show that telemetric assessment of the VMR is a sensitive tool, suitable for long-term studies in conscious rats. The results with this technique also suggest that ENDO-associated vaginal hyperalgesia involves COX activity, the feature that also underlies inflammatory pains.